Overall, region- and tissue-specific injury rates in UK summer Olympic male and female athletes - Wootten, M.; McCaig, S.; Biswas, A.; Brownlow, M.; Herrington, L.; Taylor, A.; Brown, F.; Burden, R.; Ranson, C. (British Journal of Sports Medicine, 2021)
Background Existing studies have reported that female athletes are at increased risk of particular injury types e.g. ACL rupture and bone stress injury, and have reduced risk of others e.g. hamstring injury. Other sport-specific studies have reported that female athletes generally have higher risk of injury in some sports, lower risk in others. No previous study has compared male and female injury rates across a range of summer Olympic sports.